2011
DOI: 10.4236/jsemat.2011.12006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing on Structural, Morphological, Electrical and Optical Studies of Nickel Oxide Thin Films

Abstract: Sol gel spin coating method has been successfully employed for the deposition of nanocrystalline nickel oxide (NiO) thin films. The films were annealed at 400°C - 700°C for 1 h in an air and changes in the structural, morphological, electrical and optical properties were studied. The structural properties of nickel oxide films were studied by means of X-ray diffraction (XRD) and scanning electron microscopy (SEM). XRD analysis shows that all the films are crystallized in the cubic phase and present a random or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 27 publications
5
34
0
Order By: Relevance
“…By comparing the XRD pattern with the JCPDS data, it was found that the product is nickel oxide (JCPDS file no: 73-1519). Also The prepared film, which agrees with that in the literatures P. S. Patil and L. D. Kadam, (2002) [21] V. Patil, et al (2011) [22] H. L. [23] and I. Fasaki, et al [24]. The diffragram of the new film shows one pronounced diffraction peaks, (111) appear at 2θ = 28.001˚.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…By comparing the XRD pattern with the JCPDS data, it was found that the product is nickel oxide (JCPDS file no: 73-1519). Also The prepared film, which agrees with that in the literatures P. S. Patil and L. D. Kadam, (2002) [21] V. Patil, et al (2011) [22] H. L. [23] and I. Fasaki, et al [24]. The diffragram of the new film shows one pronounced diffraction peaks, (111) appear at 2θ = 28.001˚.…”
Section: Resultssupporting
confidence: 89%
“…The band gap energy values are found to be 3.3 eV. Our result is in good agreement with S. A. Mahmoud, et al (2011) [18], P. S. Patil and L. D. Kadam, (2002) [21] and V. Patil, et al (2011)[22].…”
supporting
confidence: 95%
“…The metal oxide can assume a variety of structural geometries with an electronic structure that can exhibit metallic and semiconductor characteristics, conferring different chemical and physical properties1.…”
mentioning
confidence: 99%
“…The performances of NiO-based electrochemical energy-storage devices are related to its structural, chemical and electrical properties, which depend considerably on the preparation method. NiO has been synthesized by a variety of chemical and 35 physical approaches 14,15,[17][18][19][20][21][22] . Chemical methods including chemical bath deposition, electrodeposition, chemical precipitation, spray pyrolysis, hydrothermal process and sol gel process usually generate harmful chemical wastes or excess chemical impurities, which come from the chemical precursors or 40 other chemical agents used in the processes.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the sparking 30 process parameters were chosen based on the previous studies reported by our group 27 , which showed that higher sparking voltage could produce smaller average particle size. In particular, the maximum sparking voltage (3.0 kV) and sample sliding speed (1 cm/min) of the sparking machine were selected to 35 obtain uniform sparked films with very fine nanometer-sized particles and high porosity. The mass of sparked NiO films was measured by high-precision microbalance with 6 digit resolution (M5P, Sartorius).…”
Section: Introductionmentioning
confidence: 99%